(untitled) - 1934-; Luckey, Bud; 1952-; Cummings, Jim; Cleese, John.; 1980-; Deschanel, Zooey; (Paul A.); Felix, Paul; Ferguson, Craig; Kenny, Tom; 1882-1956.; et al. (Burbank, CA, 2011)
When sad old Eeyore loses his tail, Owl sends the whole gang--Pooh, Tigger, Rabbit, Piglet, Kanga and Roo--on a wild journey to help Eeyore and save Christopher Robin from the mysterious Backson. In the end, it turns out to be a very busy day for a bear who simply set out to find some hunny.
Keywords: Tigger (Fictitious character); Winnie-the-Pooh (Fictitious character); Drama; Eeyore (Fictitious character); Drama; Drama